From the political enemy to the enemy in the necropolitics - Álvarez Garro, Laura (2019)
This article focuses around the concept of the enemy, taking as a reference the work of Carl Schmitt, with the contributions of Sigmund Freud and Jacques Lacan. The objective of this article is to contrast the Schmitt proposal with the contributions of Freud and Lacan, with the intention of solving theoretical and practical problems. Then, it is debated whether Achille Mbembe’s proposal suggests a transformation in the idea of enmity, or if it is a sharpening of preconditions; analyzing in depth if the enemy in the necropolitics corresponds to the approach of the absolute enemy in Schmitt. Finally, we examine what are the contemporary political conditions that have led to an increase in necropower scenarios.